Electroluminescence generation in PbS quantum dot light-emitting field-effect transistors with solid-state gating - Shulga, Artem; Graf, Arko; Zaumseil, Jana (ACS nano, 2018)
The application of light-emitting field-effect transistors (LEFET) is an elegant way of combining electrical switching and light emission in a single device architecture instead of two. This allows for a higher degree of miniaturization and integration in future optoelectronic applications. Here, we report on a LEFET based on lead sulfide quantum dots processed from solution. Our device shows state-of-the-art electronic behavior and emits near-infrared photons with a quantum yield exceeding 1% when cooled. We furthermore show how LEFETs can be used to simultaneously characterize the optical and electrical material properties on the same device and use this benefit to investigate the charge transport through the quantum dot film.
Gesehen am 18.09.2019